EFEKTIVITAS PENGGUNAAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR CERPEN PADA SISWA KELAS XI MA NUSANTARA ARJAWINANGUN TAHUN 2021/ 2022 - Hidayat, Ahmad Deni; Nuryanto, Tato; Khuzaemah , Emah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This study aims to determine the effectiveness of the discovery learning model on short story learning outcomes. The method used in this study is the Quasi Experimental Design Method using the Posttest Only Control Group Design where there is an experimental class with the Discovery Learning learning model and a control class with a direct learning model, which is then given a Posttest to determine student learning outcomes after being given different treatments. . The target of this research is students of class XI Religion and XI Social academic year 2021/2022. From the research results obtained, it shows that: (1) Student learning outcomes with the Discovery Learning learning model are higher than student learning outcomes than using the conventional direct learning model with the acquisition of t-test namely tcount 23.917 > ttable 2.056 and with details of the average value the experimental class average was 87.96 and the control class average was 51.30. (2) The test results indicate that there are significant differences in results. It can be concluded that the application of the Discovery Learning learning model can increase the interest and learning outcomes of class XI MA Nusantara Arjawinangun students. Keywords: Effectiveness, Discovery Learning, Learning Outcomes